The fast fashion vs environment debate: Consumers’ level of awareness, feelings, and behaviour towards sustainability within the fast-fashion sector - Papasolomou, Ioanna; Melanthiou, Yioula; Tsamouridis, Anestis (My University, 2022)
The aim of this study is to investigate the level of knowledge (cognition), attitudes, and behaviour of customers toward sustainability issues in the context of fast fashion. It incorporates empirical evidence that focuses on investigating what consumers know and feel, and how they behave towards fast fashion brands in the context of sustainability, and further explores whether consumers’ knowledge about fashion is not sufficient to evoke environmentally friendly purchases. To facilitate a shift towards more sustainable fashion consumption if this is desirable, providing clear information about the environmental and the social impact of products and creating strong feelings, seems to be promising. The descriptive analysis of data collected from 97 consumers reveals that although most consumers claim to be knowledgeable about sustainability-related issues, they lack precise and accurate knowledge on aspects linked to the sustainable supply chain, including fabric, materials, recycling, or re-use of fashion items. Women appear to be more knowledgeable about this topic than men, but men are willing to pay a higher price for fast fashion brands that reflect their moral values.
Keywords: consumer knowledge; fast fashion; purchase behaviour; Sustainability; sustainable consumption